2000
DOI: 10.3354/meps194123
|View full text |Cite
|
Sign up to set email alerts
|

Where are the mussels on Cook Strait (New Zealand) shores? Low seston quality as a possible factor limiting multi-species distributions

Abstract: Exammation of the physiological ecology of 3 sympatncally occurring mytilids (the ribbed, blue and greenshell mussels, Aulacomya maoriana, ivlytilus galloprovincialis and Perna canalicdus, respectively) was carned out during summer and winter at 2 sites which differ markedly in their environmental characteristics (Mahanga Bay inside Wellington Harbour, where mussels are abundant, and Island Bay on the exposed Cook Strait shore, where mussels are absent). Seston components (particle counts per rnl in the size r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(151 citation statements)
references
References 20 publications
15
131
4
1
Order By: Relevance
“…Wellington Harbour is a semienclosed bay that receives significant freshwater inputs from the Hutt River (Gardner 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Wellington Harbour is a semienclosed bay that receives significant freshwater inputs from the Hutt River (Gardner 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Johnston & Leggett 2002, Gosselin & Rehak 2007, Shima & Swearer 2009). Studies spanning the last 12 yr have demonstrated that dramatic differences can be observed between both of the locations examined, with Wellington Harbour having greater densities and recruitment rates of invertebrates and fish (Phillips & Hutchison 2008, Shima & Swearer 2009, Demello & Phillips 2011, higher stocks of phytoplankton and particulate concentration (Gardner 2000, Helson et al 2007), higher quality and faster growing larval fish (Shima & Swearer 2009, and higher whelk growth rates (N. Phillips unpubl. data), all suggesting a more productive environment in Wellington Harbour.…”
Section: Hatchling Sizementioning
confidence: 99%
“…the semienclosed and nutrient-rich Wellington Harbor vs. the exposed and low productivity Wellington southern coast. Compared to the nearby southern coast, Wellington Harbour has denser and more speciesrich intertidal communities with greater recruitment rates of fish and invertebrates (Phillips & Hutchison 2008, Shima & Swearer 2009, Demello & Phillips 2011, higher standing stocks of phytoplankton and concentrations of particulates (Gardner 2000, Helson et al 2007), higher quality and faster growing larval reef fish (Shima & Swearer 2009, and higher growth rates for several species of whelks (N. Phillips unpubl. data).…”
mentioning
confidence: 99%
“…(1) We determined the concentrations of food available for mussels in ambient seawater. The role of variation in primary productivity and ambient food concentrations in explaining the structure of rocky shore communities has been largely overlooked (Bustamante et al 1995) but its potential influence on abundance and size structure of populations has been highlighted in recent years (Bustamante & Branch 1996, Gardner 2000, Menge & Branch 2001, Morgan 2001. (2) We investigated the strength of the relationship between abundance of sublittoral Baltic blue mussels and exposure regimes.…”
Section: Introductionmentioning
confidence: 99%